The Effect Of Religiousity On Saving Intention At Sharia Bank In Medan City - Ibrahim Azhary Hasibuan (Journal Basic Science and Technology, 2020)
This study aims to determine the influence of religiosity on the intention of saving in sharia banks in the city of Medan. This research uses quantitative approach with simple regression analysis technique with 100 research sample of Moslem society in Medan city which has never been saving in shari'ah bank. The measurement tool used is the scale of religiosity compiled based on Glock & Stark's religiosity dimension (2001) and the scale of savings intention based on the intention theory of Fishbein & Ajzen (1975). The result of the research shows that there is a positive influence of religiosity on the intention of saving in shari'ah bank in Medan city, which means null hypothesis (Ho) rejected, meaning there is influence of religiosity to the intention of saving at syari bank 'ah in Medan city. Based on the results of the study.